Etnomatematika pada Transaksi Jual Beli Pasar Tradisional di Solo - Mei Lestari (Universitas Indraprasta PGRI Jakarta, 2019)
This study aims to describe the ethnomstics results of buying snd selling in Javanese society, especially solo cities. This research is an exploratory study using ethnographic traditions. Solo is a city that is densely populated and thick with culture. Solo has one kingdom known as the Surakarta Hadiningrat Sunan Palace with the raja title Raja Pakubuwana. Klewer market is located next to the kasunanan palace. The data in this study were obtained from the results of interviews and ethnographic records made during the study. Data analysis was performed using the Miles & Huberman model. The result of the study obtained several mathematical concepts used by solo society, namely activity of counting and counting. Counting activity arose during the mention of buying and selling. In calculating altitude, there are several mathematical concepts, including counting algorithms. The results of this study are expected to provide inspiration and reference material for contextual mathematics learning.